2020
DOI: 10.7554/elife.55729
|View full text |Cite
|
Sign up to set email alerts
|

Axonal mechanisms mediating γ-aminobutyric acid receptor type A (GABA-A) inhibition of striatal dopamine release

Abstract: Axons of dopaminergic neurons innervate the striatum where they contribute to movement and reinforcement learning. Past work has shown that striatal GABA tonically inhibits dopamine release, but whether GABA-A receptors directly modulate transmission or act indirectly through circuit elements is unresolved. Here, we use whole-cell and perforated-patch recordings to test for GABA-A receptors on the main dopaminergic neuron axons and branching processes within the striatum of adult mice. Application of GABA depo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 87 publications
(119 reference statements)
3
52
0
Order By: Relevance
“…However, the resulting frequency-dependent synaptic depression was not observed in older animals ( Turecek et al, 2016 ), consistent with DTX- in sensitive action potential amplitudes in small boutons of mature cerebellar basket cell interneurons ( Begum et al., 2016 ). Finally, our results are consistent with large action potential amplitudes measured in thin axons of interneurons in the hippocampus ( Hu and Jonas, 2014 ; Hu et al., 2018 ) and thin dopaminergic axons in the striatum ( Kramer et al., 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, the resulting frequency-dependent synaptic depression was not observed in older animals ( Turecek et al, 2016 ), consistent with DTX- in sensitive action potential amplitudes in small boutons of mature cerebellar basket cell interneurons ( Begum et al., 2016 ). Finally, our results are consistent with large action potential amplitudes measured in thin axons of interneurons in the hippocampus ( Hu and Jonas, 2014 ; Hu et al., 2018 ) and thin dopaminergic axons in the striatum ( Kramer et al., 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, subcellular localization of GABA A Rs also profoundly determines the type of neuronal inhibition exhibited and how GABA A R-targeting drugs will modulate neuronal activity ( Kerti-Szigeti and Nusser, 2016 ; Nathanson et al, 2019 ; Kramer et al, 2020 ). The mobility and diffusion of GABA A Rs between synaptic and extrasynaptic regions are dependent on subunit composition, specific motifs within the intracellular domain of certain subunits, and the interaction of GABA A Rs with scaffolding partners such as gephyrin or radixin ( Jacob et al, 2005 ; Thomas et al, 2005 ; Loebrich et al, 2006 ; Bannai et al, 2009 ; Mukherjee et al, 2011 ; Tyagarajan and Fritschy, 2014 ; Hausrat et al, 2015 ; Hannan et al, 2019 ; Davenport et al, 2020 ).…”
Section: Recent Advances In Gaba a R Biologymentioning
confidence: 99%
“…However, conclusive anatomical evidence for GABA A and GABA B receptors located on confirmed DA axons has not yet been reported. Direct electrophysiological recordings of nigrostriatal axons strongly support the presence of functional GABA A in DA axons [ 47 ], as do the findings that GABA A and GABA B agonists and antagonists can respectively suppress and enhance DA release when evoked by discrete single electrical or optogenetic stimulus pulses of ChR2-expressing DA axons [ 34 , 36 , 37 , 39 ]. These brief (≤2 ms) and targeted stimulation paradigms would offer very limited opportunity for activation of other striatal circuits to impact on DA released by the same stimulus.…”
Section: Direct Vs Indirect Actions Of Gaba a mentioning
confidence: 99%
“…A recent study using whole-cell and perforated-patch recordings to test for GABA A receptors on the axonal segment of DA neurons within the striatum of adult mice found that the application of GABA mediated a GABA A receptor-dependent depolarisation of DA axons [ 47 ]. Despite this depolarisation, activation of axonal GABA A receptors results in the inhibition of DA release [ 36 , 37 , 39 , 47 ], in contrast to the effects of axonal GABA A receptors elsewhere that enhance synaptic transmission, outlined above. The depolarising effects of GABA A receptors were found to paradoxically inhibit DA release through underlying mediators involving shunting inhibition and depolarisation-mediated inactivation of sodium channels [ 47 ].…”
Section: Gaba a Receptor Modulation Of Da Axonamentioning
confidence: 99%